The impact of protected areas on local livelihoods in the South Caucasus; Naturschutzgebiete und ihre Auswirkungen auf die Erwerbsquellen der lokalen Anrainerbevölkerung im Südkaukasus - Johanna Schott; Talin Kalatas; Emilia Nercissians; Jan Barkmann; Vakhtang Shelia (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2016)
Nature conservation has a long tradition in the South Caucasus, a region with very high biodiversity. Alongside century old nature reserves (NR) in Azerbaijan and Georgia, two new transboundary national parks (NP) have recently been created in Armenia and Georgia. All of these protected areas exert an influence on the local populations, which use land located inside or in proximity to these areas. To investigate the impact of protected areas on the local populations, we conducted a qualitative study close to two neighbouring, historical NRs in Georgia (Lagodekhi) and Azerbaijan (Zaqatala), and close to the two new transboundary NPs in Armenia (Lake Arpi) and in Georgia (Javakheti). We collected the opinions of the local populations, local administrations, and environmental NGOs regarding the impact of protected areas on the livelihoods of the local populations and investigated whether the local populations developed strategies for dealing with these impacts. Results show that the land use restrictions entailed by protected areas cause conflicts of interests between the goals of conservation and those of the local populations on the one hand, and competition between different local groups with regard to scarce resources such as pastures on the other hand. These land use restrictions are due to the land use regulations of the protected areas and concern the use of pastures and forests. All sorts of tourism could provide a possible solution to settle conflicts and to increase incomes. – – Naturschutz hat eine lange Tradition im Südkaukasus, einer Region, die sich durch eine hohe Biodiversität auszeichnet. Neben über hundert Jahre alten Naturschutzgebieten in Aserbaidschan und in Georgien wurden kürzlich zwei neue grenzübergreifende Nationalparks in Armenien und Georgien eingerichtet. Alle diese Schutzgebiete haben Auswirkungen auf die lokale Anrainerbevölkerung, welche Land innerhalb oder in der Nähe dieser Gebiete nutzt. Um die Auswirkungen von zwei benachbarten, historischen Schutzgebieten in Georgien (Lagodekhi) und in Aserbaidschan (Zaqatala) sowie von zwei neuen grenzübergreifenden Nationalparks in Armenien (Lake Arpi) und in Georgien (Javakheti) auf die lokale Bevölkerung zu untersuchen, führten wir eine qualitative Studie durch. Zentrale Fragestellungen der Studie betrafen zum einen die Ansichten der lokalen Bevölkerung, der lokalen Verwaltung und von Umwelt-Nichtregierungsorganisationen hinsichtlich der Auswirkungen von Schutzgebieten auf den Lebensunterhalt der Anrainerbevölkerung und zum anderen mögliche Strategien der Anrainerbevölkerung für den Umgang mit den Auswirkungen der Schutzgebiete. Die Ergebnisse zeigen, dass Landnutzungsbeschränkungen, die durch die Schutzgebiete hervorgerufen werden, einerseits Interessenkonflikte zwischen den Zielen des Naturschutzes und den Zielen der Anrainerbevölkerung hervorrufen können, und andererseits Rivalitäten zwischen verschiedenen lokalen Gruppen in Bezug auf knappe Ressourcen wie Weideland. Landnutzungsbeschränkungen sind eine Folge der Landnutzungsbestimmungen der Schutzge und betreffen den Zugang zu Weideland und Wäldern. Verschiedene Arten von Tourismus könnten eine mögliche Lösung darstellen, um bestehende Konflikte zu lösen und um die Einkommen der lokalen Bevölkerung zu verbessern.
urn:nbn:de:gbv:3:2-53089
Keywords: Q56; O13; O53; Z1; 330; Transcaucasia; nature conservation; qualitative research; protected areas; rural livelihoods; Südkaukasus; Naturschutz; qualitative Forschung; Schutzgebiete; ländlicher Lebensunterhalt